Dynamics in the concentrations of health-promoting compounds: lupeol, mangiferin and different phenolic acids during postharvest ripening of mango fruit. - Vithana, M.; Singh, Z.; Johnson, Stuart (John Wiley and Sons Inc., 2017)
BACKGROUND: Mango fruit (Mangifera indica L.) is renowned for its pleasant taste and as a rich source of health beneficial compounds. The aim of this study was to investigate the changes in concentrations of health-promoting compounds viz., ascorbic acid, carotenoids, antioxidants, lupeol, mangiferin, total phenols, individual phenolic acids as well as ethylene production and respiration rates during climacteric ripening in 'Kensington Pride' and 'R2E2' mango fruit. RESULTS: The climacteric ethylene and respiration peaks were noted on the third day of fruit ripening period. The concentrations of total carotenoids in the pulp, total antioxidants in both pulp and peel, total phenols of the peel, lupeol, and mangiferin were significantly elevated, whilst the concentration of ascorbic acid declined during post-climacteric ripening. Gallic, chlorogenic and vanillic acids were identified as the major phenolic acids in both pulp and peel of 'Kensington Pride' and 'R2E2' mangoes. The concentrations of phenolic acids (gallic, chlorogenic, vanillic, ferulic and caffeic acids) also increased during the post-climacteric phase. The concentrations of all phenolic compounds were several-fold higher in the peel than pulp. CONCLUSION: Mangoes at post-climacteric ripening phase offer the highest concentrations of health-promoting compounds. Peel, at this stage of fruit ripening could be exploited as a good source for extraction of these compounds.